A STUDY ON THE CAUSES OF FIVE DROPOUT STUDENTS OF CHAKALAGHAT IN NAGAON DISTRICT AT SECONDARY LEVEL OF EDUCATION - HIMAKSHI BORAH (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Dropout is a major problem of our education system in Assam. Assam has registered as the highest dropout rate in primary and secondary classes in the country. It is important to solve this problem by found the root causes of it. So in this study the researcher studied about five dropout student of Chakalaghat in Nagaon district. It was found that so many household factors, individual child factor and school related factors related to this problem. So we have to solve these problems to overcome this problem.